China, its history, arts, and literature - Brinkley, Captain F. (J. B. Millet Co., 1902)
This book introduce about preconventional period ò foreign intercourse and trade. The propaganda and Chinese religions, conventional period, education, literati, secret societies, and rebellions. The second ửa and the events preceding.